The association of aspirin use with age-related macular degeneration progression in the Age-Related Eye Disease Studies: AREDS2 Report No. 20 - Keenan, Tiarnan D (Ophthalmology, 2019)
PURPOSE: To analyze the potential association between aspirin use and progression of age-related macular degeneration (AMD). DESIGN: Two prospective cohort studies within two controlled clinical trials of oral supplementation for age-related eye disease. PARTICIPANTS: Age-Related Eye Disease Study (AREDS) participants, aged 55 to 80 years, and AREDS2 participants, aged 50 to 85 years. METHODS: Propensity scores for aspirin use were calculated for AREDS and AREDS2 participants, separately, by logistic regression. Of the participants without late AMD (geographic atrophy (GA) or neovascular AMD) in either eye at study baseline, aspirin users were matched 1:1 with non-users by propensity score (separately for AREDS and AREDS2). Proportional hazards regression was performed, adjusting for age, on the matched participants to evaluate associations between aspirin propensity score and progression to late AMD (and its subtypes). MAIN OUTCOME MEASURES: Progression to late AMD on color fundus photographs, graded centrally. RESULTS: Of the 3734 eligible AREDS participants, 1049 (28.1%) were taking aspirin and 2685 (71.9%) were not. The equivalent figures in AREDS2 were 1198 (49.9%) and 1205 (50.1%), respectively. Following matching by propensity score, the characteristics of the users and non-users were similar, in both studies. Of the 1950 matched AREDS participants and 1694 matched AREDS2 participants, over median follow-up of 10.1 years (AREDS) and 5.0 years (AREDS2), the numbers who progressed to late AMD, GA, or neovascular AMD were 454 (23.3%), 345 (17.7%), and 278 (14.3%), respectively, in AREDS, and 643 (38.0%), 402 (24.6%), and 341 (20.1%), in AREDS2. The hazard ratios of progression in quintile 5 (highest propensity for aspirin use) versus 1 (reference) were 1.17 (p=0.35), 1.24 (p=0.25), and 0.95 (p=0.81), respectively, in AREDS, and 1.26 (p=0.09), 1.46 (p=0.03), and 1.12 (p=0.58), in AREDS2. No significant association with progression to late AMD was observed for any quintile 2–5, for any of the three outcomes, in either study. CONCLUSIONS: Aspirin use was not significantly associated with progression to late AMD, or its subtypes, in either the AREDS or the AREDS2. Patients with AMD need not avoid aspirin for this reason, when its use is medically indicated.